Connecting Sediment Retention to Distributary‐Channel Hydrodynamics and Sediment Dynamics in a Tide‐dominated Delta: The Ayeyarwady Delta, Myanmar. Issue 3 (18th March 2021) - Glover, H. E.; Ogston, A. S.; Fricke, A. T.; Nittrouer, C. A.; Aung, Cherry; Naing, Thet; Kyu Kyu, Khin; Htike, Htike
Abstract: The largest deltas on Earth are tide‐dominated with multiple distributaries, which can experience different forcings. Yet, most observational studies of sediment dynamics in these systems focus on a single distributary. Comparison of the tidal‐to‐estuarine reaches of three representative distributaries of the Ayeyarwady Delta, Myanmar highlights the variability in sediment retention and export within a megadelta. The Ayeyarwady River has no mainstem dams, providing an opportunity to examine a relatively natural, monsoon‐dominated system. Observations were collected during high flow (September 2017) and low flow (March 2018 and 2019). The eastern Yangon distributary empties into the sheltered Gulf of Mottoma while the central Bogale and western Pathein distributaries are exposed to seasonal waves. During high flow, suspended‐sediment concentration (SSC) was consistent across all three distributaries (0.2–0.4 g/L). The upper delta retained 20%–60% of the mainstem sediment load, while the lower distributaries were tidal rivers exporting sediment. During low flow, the lower distributaries were partially mixed estuaries with little net discharge. However, SSC increased to >1 g/L in the Yangon distributary, remained constant in the Bogale distributary, and decreased in the Pathein distributary compared to high flow. This difference was driven by offshore sediment supply; fine sediment is retained near the mouth of the Yangon and advected away from the Pathein distributary. Consequently, nearshore sediment residence time in monsoon‐influenced megadeltas is controlled by coastal orientation, the timing of discharge with respect to ocean conditions, and tidal amplification. Changes to fluvial sediment delivery can cause non‐uniform coastal impacts due to these differing distributary processes. Key Points: Individual distributaries of tropical megadeltas can exhibit significantly different hydrodynamics and sediment transport processes In the Ayeyarwady Delta, low‐flow estuarine processes import offshore sediment into distributaries when offshore sediment is available and resuspended Sediment residence time in the nearshore is controlled by tidal amplification and the coastal orientation with respect to monsoon winds